DANA PENSIUN MENURUT HUKUM ISLAM DAN HUKUM POSITIF - Mahmud, Muhammad (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This study aims to determine: the practice of managing pension funds according to Islamic law and positive law, as well as the similarities and differences in the management of pension funds in Islamic law and positive law. This study uses the library research method, which means that the collection of data or materials needed in writing this thesis comes from books, scriptures, theses, journals and theses. The results of this study indicate that the practice of managing pension funds according to Islamic law is appropriate as long as the pension fund is not used as a deposit and the pension fund is immediately withdrawn, not stored in the banking system, worrying that the bank is still a conventional system. The practice of managing pension funds according to positive law: A pension fund is an income received every month by an employee who is no longer able to work, to finance his next living, so that he is not left stranded when he is powerless to find other income. Article 1 Point 4 of Law Number 11 of 1992, states that a financial institution pension fund is a pension fund established by a bank or life insurance company, to administer a defined contribution pension program for individuals. Similarities and differences in pension fund management in Islamic law and positive law. Pension fund management in Islam is based on a contract agreed upon by both parties and does not contain usury, maisir, tadlis, gharar and other elements prohibited in Islam, while in conventional it uses general management laws and does not involve both parties. initial agreement, so that there are fears of elements that are prohibited from transactions that are prohibited in Islam. The similarity is that they manage funds with the aim of providing benefits to retired customers when they are no longer working in government agencies.